Soil renewal and metal ions pollutants removal in water by using volcanic ash from Mt. Sinabung and Mt. Merapi eruptions - Raudhatu Shofiah; Dian Fiantis; Amrizal Saidi; Roslan Ismail (Jurnal Ilmiah Pertanian, 2022)
Volcano activities form about 22% of Indonesian landforms; 35 are Sumatra volcanoes with many sources of volcanic ash. Mt. Sinabung and Mt. Merapi were the most significant eruptions issuing abundant material. This study aims to identify volcanic ash's morphological, mineralogical, and chemical properties from both volcanoes. This study also determines their optimum adsorption capacity in removing water pollutant materials, especially iron (Fe3+) and aluminum (Al3+). This study began by identifying the properties of the sample, such as color, pH H2O and KCl, chemical composition with XRF, exchangeable bases-cation exchange capacity, and mineral identification by using XRD and SEM. Then, batch adsorption studies were performed to determine the adsorption capacity of volcanic ash. Volcanic ash samples were gray to light gray with pH 2.9 – 5 and contained silicate minerals, i.e., feldspar, quartz, plagioclase, magnetite, and gypsum. Volcanic ash consisted of rich material that was important for increasing soil nutrients. The macronutrient of Mt. Sinabung in the order of Ca, Mg, K, S, P, and Mt. Merapi of S, Ca, Mg, K, and P act as sources of soil renewal. The adsorption capacity of volcanic ash to adsorb Al3+ and Fe3+ from water pollutants increased after the temperature reached 90oC, and pH tends to be less acidic.